Peran Electronic Commerce dalam Pemasaran Kewirausahaan untuk Mengembangkan Kinerja UMKM - Stivaniyanti Atmanegara; I Dewa Made Yuda Mahendra; Emha Diambang Ramadhany; Dewi Masruroh; Elinda Wati (Universitas Nusantara PGRI Kediri, 2023)
Starting from smartphones, netbooks, computers, to other devices, the internet has played an important role in shaping our new way of life. One new aspect that has emerged is online shopping, where people can now shop easily through online platforms. This phenomenon is often referred to as electronic commerce (electronic commerce or e-commerce). In business, it is important to implement e-commerce in marketing, sales and customer service activities. Many people think that marketing through the internet is more effective than traditional marketing methods because it overcomes various obstacles such as difficulty entering the market, country restrictions, and the lack of rules that apply in conventional marketing. This study is a quantitative research with a descriptive approach. Based on the research and debate that has been done, the components of overall income, business standards, the type of e-commerce media used, and the number of visitors to e-commerce media have a minimal negative effect on the growth of micro and small businesses. This conclusion is supported by the fact that the benefits derived from implementing e-commerce in the micro and small business sector are more focused on long-term benefits that are not directly related to increasing income directly.